MODEL IJTIHAD SAINTIFIK DALAM PENENTUAN WAKTU IBADAH - Zaenul Arifin (Institut Agama Islam Negeri Metro, 2015)
The style of reading text is ideally through three stages, they are “qira'ah salafiyya”, “qira'ah ta'wiliyyah”, and “qira'ah maqashidiyyah”. While in the area of “​​al-waqi'” (the fact) there are several disciplines of knowledge that are used in understanding social phenomena, politics, and science. Therefore, when we are reading the text that will be focus on science phenomenon, the context should be interrelated to the existing disciplines of knowledge in the area of ​​“al-waqi'”. If we do not apply it, the understanding of the text will be out of date, so it is not aplicable. Therefore the “ijtihad” must be always inflamed and the door of “ijtihad” will never be closed. In the context of inflaming “ijtihad”, the knowledge of “usul fiqh” is known as a set of standard methodology that its role has been proven by Islamic thinkers such as Imam madzhab in digging an Islamic law from its original source (al-Qur'an and Sunnah). But today, the “fiqh” of Islam is considered barren because the role of theoretical framework of “usul fiqh” is less relevant to answer the contemporary problems. Therefore, there are many models of “ijtihad” with a new methodology from contemporary Islamic experts in an attempt to dig Islamic law from its original source to suit the dynamics of the progress of time, one of the models of “ijtihad” scientific is timing of prayers. This is a big job to be done in order to establish Islamic ideals themselves (self image of Islam) in the midst of modern life that it is constantly changing and evolving. In Indonesia, the last decade has emerged the development of Islamic law which is adapted to the real conditions of life in Indonesia. This is motivated by the realization that the classical “fiqh” with its methodology device are not able to answer the contemporary issues, so we need a scintific model of “ijtihad”.